Fast photovoltaic IncCond-MPPT and backstepping control, using DC-DC boost converter - Mohamed Moutchou; Atman Jbari (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, we present our contribution in photovoltaic energy optimization subject. In this research work, the goal is to determinate fastly the optimal PV Module working point, allowing maximum power extraction. In this work we use DC-DC Boost converter to control the working point, by adjusting PV voltage trough duty cycle. In order to achieve our goal, we use the combination of incremental conductance MPPT technique and DC-DC Boost converter backstepping control. The validation of this control is made by Matlab simulation; the obtained results prove its effectiveness and its good maximum power tracking dynamics for different irradiance and temperature profiles.